Engineering Vaccines to Reprogram Immunity against Head and Neck Cancer. (June 2018) - Tan, Y.S.; Sansanaphongpricha, K.; Prince, M.E.P.; Sun, D.; Wolf, G.T.; Lei, Y.L.
The recent Food and Drug Administration's approval of monoclonal antibodies targeting immune checkpoint receptors (ICRs) for recurrent or metastatic head and neck squamous cell carcinoma (HNSCC) offers exciting promise to improve patient outcome and reduce morbidities. A favorable response to ICR blockade relies on an extensive collection of preexisting tumor-specific T cells in the tumor microenvironment (TME). ICR blockade reinvigorates exhausted CD8 + T cells and enhances immune killing. However, resistance to ICR blockade is observed in about 85% of patients with HNSCC, therefore highlighting the importance of characterizing the mechanisms underlying HNSCC immune escape and exploring combinatorial strategies to sensitize hypoimmunogenic cold HNSCC to ICR inhibition. Cancer vaccines are designed to bypass the cold TME and directly deliver cancer antigens to antigen-presenting cells (APCs); these vaccines epitomize a priming strategy to synergize with ICR inhibitors. Cancer cells are ineffective antigen presenters, and poor APC infiltration as well as the M2-like polarization in the TME further dampens antigen uptake and processing, both of which render ineffective innate and adaptive immune detection. Cancer vaccines directly activate APC and expand the tumor-specific T-cell repertoire. In addition, cancer vaccines often contain an adjuvant, which further improves APC function, promotes epitope spreading, and augments host intrinsic antitumor immunity. Thus, the vaccine-induced immune priming generates a pool of effectors whose function can be enhanced by ICR inhibitors. In this review, we summarize the major HNSCC immune evasion strategies, the ongoing effort toward improving HNSCC vaccines, and the current challenges limiting the efficacy of cancer vaccines.